The Role Of Business Model Innovation, Trust, And Customer Commitment In Sme Business Growth (A Study On Gamelan Craft Sme Business In Special Region Of Yogyakarta) - Bayu Aji Laksono; Al Hasin (International Journal of Economics, Business and Innovation Research, 2025)
The purpose of this study was to investigate how customer loyalty, trust, and innovative business models affect the expansion of small and medium enterprises (SMEs), especially the gamelan craft SME "Special Region of Yogyakarta." Using quantitative methodology, this study collected data from up to 130 employees, managers, and owners of SMEs using questionnaires. The validity and reliability of the research instruments were tested through statistical data processing using SEM PLS and SPSS. The results of the study indicate that: 1) Business model innovation has a positive and significant effect on SME business growth; 2) Customer trust has a positive and significant effect on SME business growth; and 3) Business model innovation has a positive effect on SME business growth, which is mediated by customer commitment. The findings of this study indicate that in order to increase company growth, Special Region of Yogyakarta SME Managers must continue to promote innovation in business models, which include implementing digital technology and modernizing marketing tactics. Furthermore, management needs to concentrate on increasing consumer commitment and trust by improving the quality of goods and services and developing loyalty plans that will strengthen long-term relationships with clients.